2009
DOI: 10.1128/jb.01425-08
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the LuxR-Type Transcriptional Regulator RamA in Regulation of Expression of thegapAGene, Encoding Glyceraldehyde-3-Phosphate Dehydrogenase ofCorynebacterium glutamicum

Abstract: SugR, RamA, GlxR, GntR1, and a MarR-type transcriptional regulator bind to the promoter region of the gapA gene encoding glyceraldehyde-3-phosphate dehydrogenase (GAPDH), essential for glycolysis in Corynebacterium glutamicum. We previously showed that SugR, a transcriptional repressor of phosphotransferase system genes for the sugar transport system, is involved in the downregulation of gapA expression in the absence of sugar. In this study, the role of RamA in the expression of the gapA gene was examined. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…Thus, the changes in the level of sugR expression in the pCRC622-carrying strain seemed to be correlated with those in the level of ramA expression. This is consistent with the finding that RamA directly activates sugR expression (31).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Thus, the changes in the level of sugR expression in the pCRC622-carrying strain seemed to be correlated with those in the level of ramA expression. This is consistent with the finding that RamA directly activates sugR expression (31).…”
Section: Resultssupporting
confidence: 82%
“…This is supported by the findings that the activity of the ramA promoter in the ramA mutant background was comparable to that in the sugR-ramA mutant background (Table 2). In this context, it should be noted that RamA acts as a transcription activator of sugR and sugR mRNA is markedly downregulated by ramA deletion (31). We further confirmed that ␤-galactosidase activity of the sugR promoter-lacZ fusion in the ramA mutant background was undetectable (data not shown).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations